Struktur Kepemilikan Keluarga dan Kinerja Perusahaan pada Sektor Aneka Industri - Finda Yovita; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This study aimed to prove the influence of family ownership on firm performance measured by ROA. The control variables used in this research were GCG Score, Intensity of Competition and firm size. This study used a sample of companies listed in the Indonesia Stock Exchange (IDX) in miscellaneous industries sector for the period 2010-2015 then measured through software Statistical Package for the Social Sciences (SPSS). The results of this study indicated that family ownership and intensity of competition had no influence on firm performance. Meanwhile, GCG and firm size had a positive influence to firm performance that measured by ROA.